2011
DOI: 10.2133/dmpk.dmpk-11-rg-039
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Pharmacokinetics and Pharmacodynamics of Anesthetic Agent Propofol with Regard to CYP2B6 and UGT1A9 Genotype and Patient Age

Abstract: Propofol (2,6-diisopropylphenol) is administered intravenously for induction and maintenance of anesthesia; however, cases of progressive myocardial failure (propofol syndrome) related to the use of propofol have been reported. In the present study, the individual differences in pharmacokinetics and/or pharmacodynamics of propofol were investigated in patients who were genotyped for CYP2B6 and UGT1A9. Fifty-one patients treated with propofol in St. Marianna University Hospital were recruited for this study and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
25
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 19 publications
5
25
2
1
Order By: Relevance
“…The elution profiles of propofol were monitored fluorometrically at an excitation wavelength of 270nm and an emission wavelength of 310 nm. Plasma concentrations of propofol were kinetically analyzed by Phoenix WinNonlin software version 6 (Pharsight, Mountain View, CA, USA) using a two-compartment analysis 15) . We then calculated the half-life of distribution (t 1/2 α) and elimination (t 1/2 β) and the area under the blood concentration-time curve for 60 min (AUC 0-60 ).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The elution profiles of propofol were monitored fluorometrically at an excitation wavelength of 270nm and an emission wavelength of 310 nm. Plasma concentrations of propofol were kinetically analyzed by Phoenix WinNonlin software version 6 (Pharsight, Mountain View, CA, USA) using a two-compartment analysis 15) . We then calculated the half-life of distribution (t 1/2 α) and elimination (t 1/2 β) and the area under the blood concentration-time curve for 60 min (AUC 0-60 ).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%
“…The biotransformation of propofol is greatly dependent on liver metabolism [17][18][19], and cytochrome P450 (CYP) 2B6 and uridine diphosphate (UDP)-glucuronosyltransferase (UGT) 1A9, the main enzymes involved in propofol metabolism, are responsible for the hydroxylation and glucuronidation of propofol [20][21][22]. Single-nucleotide polymorphisms (SNPs) in CYP2B6 and UGT1A9 might contribute to the inter-individual variability in the rate of formation of propofol metabolites [21][22][23], while several studies reported no significant effect of these SNPs on propofol metabolism [7,8,10,24].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have attempted to test whether the polymorphic CYP2B6 gene results in any significant differences in propofol clearance and consciousness following bolus doses and infusions, but none have resulted in recommendations for gene-guided propofol dosage adjustments [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%